2012
DOI: 10.1007/s00122-012-1838-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL for resistance to eyespot of wheat in Aegilops longissima

Abstract: Eyespot is an economically important disease of wheat caused by the soilborne fungi Oculimacula yallundae and O. acuformis. These pathogens infect and colonize the stem base, which results in lodging of diseased plants and reduced grain yield. Disease resistant cultivars are the most desirable control method, but resistance genes are limited in the wheat gene pool. Some accessions of the wheat wild relative Aegilops longissima are resistant to eyespot, but nothing is known about the genetic control of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 45 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…(1998) observed that resistance to the two pathogen species could be conferred by different genes. Similarly, Sheng and Murray (2009) observed that 20% of the A. longissima lines they tested responded differently to the two species, and Burt et al. (2010) identified four T. monococcum lines that responded differently to the two species.…”
Section: Durability Of Eyespot Resistance Genesmentioning
confidence: 89%
See 2 more Smart Citations
“…(1998) observed that resistance to the two pathogen species could be conferred by different genes. Similarly, Sheng and Murray (2009) observed that 20% of the A. longissima lines they tested responded differently to the two species, and Burt et al. (2010) identified four T. monococcum lines that responded differently to the two species.…”
Section: Durability Of Eyespot Resistance Genesmentioning
confidence: 89%
“…intermedium (Li et al. 2004, 2005), and Aegilops longissima (Sheng and Murray 2009). Immune and highly resistant accessions were also identified in T. tauschii with a non‐transformed strain (Assefa and Fehrmann 1998).…”
Section: Sources Of Eyespot Resistance and Resistance Genes Found In mentioning
confidence: 99%
See 1 more Smart Citation
“…In T. monococcum, resistance for eyespot disease was found (Murray et al 1994 ), which was later transferred to the cultivated gene pool (Cadle et al 1997 ;Sheng et al 2012 ). Thus, in order to make use of the insect/pest resistance identifi ed in several different alien sources a large collection of synthetic wheat lines were developed at the International Maize and Wheat Improvement Center, CIMMYT, and are currently being used in several breeding programs around the globe (Mujeeb-Kazi and Rajaram 2002 ).…”
Section: Breeding For Biotic Stress Resistancementioning
confidence: 99%
“…Aegilops species has attracted much attention since it has desirable gene resources and is widely used for wheat drought-resistance improvement (Zaharieva et al 2001; Molnár et al 2004). Particularly, Aegilops longissima (2n = 2x = 14, S l S l ) was shown to have eyespot and pre-harvest sprouting resistance (Sheng et al 2012; Singh et al 2013), and superior glutenin genes (Wang et al 2013). However, the gene resources for drought resistance in 1S l genome is not yet being explored and utilized so far.…”
Section: Introductionmentioning
confidence: 99%